2022
DOI: 10.1021/acsaelm.2c00705
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Narrow-Band Green Light-Emitting Hybrid Halides for Wide Color Gamut Display

Abstract: Phosphors with narrow-band emission are in great demand for liquid crystal display backlighting applications. In this work, four zero-dimensional Mn 2+ -based organic−inorganic metal halides (OIMHs), (C 13 H 26 N) 3 MnBr 4 •Br, (C 13 H 26 N) 2 MnCl 4 , and (C 7 H 18 N) 2 MnX 4 (X = Cl, Br), were synthesized, and their crystal structures were solved. Under blue-light excitation, all of the materials exhibited bright narrow-band green luminescence centered at 515−525 nm with high photoluminescence quantum yields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…OIMH perovskites have flexible and adjustable structures, such as the constituent component including the selection of organic molecules, metal and halogen elements, structural dimension, and electronic structures . The dispersed organic ligands and inorganic parts endow OIMH perovskites with excellent photoelectric performances, which make them good candidates in the fields of solar cells, light-emitting diodes (LEDs), nonlinear optical (NLO) crystals, , etc. Perovskite photoelectric materials have developed rapidly, with photovoltaic efficiency increasing from 4 to 25.7% in 10 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OIMH perovskites have flexible and adjustable structures, such as the constituent component including the selection of organic molecules, metal and halogen elements, structural dimension, and electronic structures . The dispersed organic ligands and inorganic parts endow OIMH perovskites with excellent photoelectric performances, which make them good candidates in the fields of solar cells, light-emitting diodes (LEDs), nonlinear optical (NLO) crystals, , etc. Perovskite photoelectric materials have developed rapidly, with photovoltaic efficiency increasing from 4 to 25.7% in 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…The first two-dimensional (2D) Ge-based perovskite, (C 4 H 9 NH 3 ) 2 GeI 4 , was synthesized by Mitzi in 1996, which exhibited a broad PL with a peak at around 690 nm . In 2015, Kanatzidis and co-workers reported a series of Ge-based perovskites with three-dimensional and one-dimensional structures, but their PL behaviors were unknown . In 2017, Han et al successfully synthesized 2D perovskite (PEA) 2 GeI 4 (PEA = C 6 H 5 C 2 H 4 NH 3 + ), which showed a wide PL with an emission peak located at 630 nm and a PLQY of 0.6% .…”
Section: Introductionmentioning
confidence: 99%
“…In order to explore the factors influencing the fwhm, the structural parameters and PL characteristics for compounds 1 and 2 are listed in Table 1, together with those of other Mn( ii ) tetrahedral bromide hybrids with similar cyclic organic cations reported in previous literature. 12,15,16,27,28,43,44 As highlighted in Fig. 3, a strong dependence is observed between the fwhm values of their green emission and the bond length distortion degree ( λ tet ) of the Mn tetrahedron, where the smaller the λ tet value is the narrower the fwhm is.…”
Section: Resultsmentioning
confidence: 90%
“…24,25 Although the 0D tetrahedral Mn(II) OIMHs exhibit similar crystal structures and luminescence behaviors, their fwhm values in the PL spectra still differ in the range from 35-65 nm. [11][12][13][14][15][26][27][28] The regulation of fwhm is crucial, considering that the narrower the fwhm, the wider the color gamut can be achieved in the fabricated LEDs. 29 Concerning the factors influencing fwhm, Kovalenko's group demonstrated that by selecting halogens (chloride, bromide or iodide), fwhm can be regulated through the altered ligand-field effects and spinorbit coupling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation